Can we prove the existence of completely random events? - Kuś, Marek (Philosophical Problems in Science (Zagadnienia Filozoficzne w Nauce), 2018)
I show how classical and quantum physics approach the problem of randomness and probability. Contrary to popular opinions, neither we can prove that classical mechanics is a deterministic theory, nor that quantum mechanics is a nondeterministic one. In other words it is not possible to show that  randomness in classical mechanics has a purely epistemic character and that of quantum mechanics  an ontic one.  Nevertheless, recent developments of quantum theory and increasing experimental possibilities to check its predictions call for returning to the problem of comparing possibilities given by classical and quantum physics to accommodate and prove the existence of a `genuine randomness'.  Recent results  concerning `amplification of randomness' show that, in certain sense,  quantum physics is in fact  ‘more random’ that classical and outperforms it in producing a `truly random process'.
Keywords: randomness; ontic and epistemic randomness; randomness in classical and quantum physics; randomness enhancement; amplification of randomness